Peran Kepercayaan Memediasi Hubungan Reputasi dan Intensi Pembelian di E-Commerce - Kusumawati, Ratna Dewi; Diyani, Lucia Ari (JURNAL ONLINE INSAN AKUNTAN; Vol 6 No 1 (2021): Jurnal Online Insan Akuntan (Juni 2021)DO - 10.51211/joia.v6i1.1471, 2021)
T his research is  conducted to discover the mediation role of trust, especially trust to seller in e-commerce , to  seller reputation and purchase intention relationship in e-commerce. Data in this research is collected using questionnaire. Data in this research is analyzed using Path Analysis and Sobel Test. Finding in this research shows that trust to seller is able to mediate the relationship between reputation and purchase intention in e-commerce. Other findings in this research is reputation variable affect purchase intention directly in statistic test, and reputation variable is affecting trust to seller variable and trust to seller variable significantly affect purchase intention variable. T he finding  is expected to contribute in providing new insights in accounting information systems research, especially related to e-commerce in Indonesia  and  are expected to provide reference contributions for future studies in the same field.